2013
DOI: 10.1002/jgrg.20075
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variability of dissolved organic matter in the Cariaco Basin

Abstract: [1] Dissolved organic carbon (DOC), nitrogen (DON), and phosphorus (DOP) were measured monthly at the CARIACO Time Series station (10 30 0 N, 64 40 0 W) in the southeastern Caribbean Sea between 2005 and 2012. Marked seasonal variability in DOC concentrations was observed, with lower values (~66 mM) in the upper water column (<75 m) during the upwelling season (December-April) due to the injection of cool, DOC-impoverished Subtropical Underwater from the Caribbean Sea. During the rainy season (May-November) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 80 publications
1
10
0
3
Order By: Relevance
“…For one cruise (December 2008), TSPP was observed to be almost five times higher in the redoxcline than in the upper 100 m. These large scale enrichments in the redoxcline are similar to patterns observed in other systems, e.g., Effingham Inlet (Diaz et al, 2012). Lorenzoni et al (2013) showed that while DOC concentrations remain relatively constant across the Cariaco Basin redoxcline, dissolved organic P (DOP) concentrations are elevated, exceeding waters immediately above and below the redoxcline by~20-40 nM. In contrast, dissolved inorganic P concentrations, or phosphate, steadily increase below the mixed layer and across the redox transition, with no obvious peak in phosphate concentrations observed at the redoxcline (Scranton et al, 2014).…”
Section: Biotic Transformations Of Suspended Psupporting
confidence: 71%
“…For one cruise (December 2008), TSPP was observed to be almost five times higher in the redoxcline than in the upper 100 m. These large scale enrichments in the redoxcline are similar to patterns observed in other systems, e.g., Effingham Inlet (Diaz et al, 2012). Lorenzoni et al (2013) showed that while DOC concentrations remain relatively constant across the Cariaco Basin redoxcline, dissolved organic P (DOP) concentrations are elevated, exceeding waters immediately above and below the redoxcline by~20-40 nM. In contrast, dissolved inorganic P concentrations, or phosphate, steadily increase below the mixed layer and across the redox transition, with no obvious peak in phosphate concentrations observed at the redoxcline (Scranton et al, 2014).…”
Section: Biotic Transformations Of Suspended Psupporting
confidence: 71%
“…La comparación de las variables ambientales y de la abundancia zooplanctónica entre los meses y estaciones se realizó con el análisis de Kruskal-Wallis. Posteriormente se procedió a dividir los meses en dos períodos, de acuerdo a la estacionalidad de la zona (Lorenzoni et al 2013, López-Monroy & Troccoli 2015, época de surgencia (marzo, abril y mayo) y época de relajación (junio, julio y agosto) y las estaciones también fueron divididas en dos grupos, de acuerdo con su ubicación, correspondiendo la zona externa (estaciones 1,2,3) a las ubicadas en la entrada y la zona interna (estaciones 4,5,6) correspondientes al interior de la laguna. Las comparaciones de las 2 zonas y de los períodos estudiados, se realizaron con la prueba de Mann-Whitney.…”
Section: Materiales Y Métodosunclassified
“…An interesting finding was that in non-upwelling months, for example July 2002, uncharacteristically high values (5 mg C m -3 h -1 ) were measured. These values are influenced by a secondary upwelling caused by the regional geostrophic flow FEBRES-ORTEGA; MULLER-KARGER et al, 2001;LORENZONI et al, 2013). The high productivity is reflected in the annually integrated values which exceed 600 g C m -3 h -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of organic carbon is a source of marine dissolved organic matter (DOM), which is one of the largest reservoirs of reduced carbon in the ocean. Thus small changes in the cycling of DOM can have dramatic impacts on the magnitude of CO 2 released or sequestered by marine systems (~662 Pmol C) (HANSELL et al, 2009;LORENZONI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation